Exploring Enhanced Military Ethics and Legal Compliance through Automated Insights: An Experiment on Military Decision-making in Extremis - Lekea, Ioanna; Lekeas, George; Topalnakos, Pavlos (Conatus - Journal of Philosophy, 2023)
Numerous factors are known to impact human decision-making: fatigue, stress, fear, sleep deprivation, organizational culture, ethics, and even substances consumed, among others. Making decisions within the context of a military operation poses exceptional challenges. Time constraints are consistently tight, and military personnel often contend with physical and mental exhaustion, along with substantial stress and fear. Our proactive strategies for addressing these hurdles predominantly revolve around educating military personnel, incorporating both theoretical training and immersive simulations that may include different types of war games, role playing and VR applications that mimic real-world challenges. However, can we extend our efforts further to ensure that military personnel surmount difficulties and consistently make morally and legally sound decisions amidst exceptional situations? Moreover, where does trust lie: in the insights of a comrade, a commanding officer, or the guidance provided by sophisticated algorithms and Artificial Intelligence (AI) systems? Could AI potentially outperform human guidance when it comes to elevating the ethical and legal discernment of military personnel amid the intensity of combat situations?